Situation Report: Hungary, 18 June 1980 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian General Elections Hungarian-West German Economic Relations Expanded Company Cafeterias - A Fundamental Social Benefit Budapest International Spring Fair 1980 Book Week Agricultural Experts Step Up Study Trips Abroad The Mutual Aid Fund: An Aid to Greater Agricultural Self-Management